Failing in corporate governance and warning signs of a corporate collapse - Ghulam Abid; Alia Ahmed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
History of corporate world is fraught with manipulations and scams. These corporate frauds are widespread, costly, and multifaceted and adversely affect all stakeholders. Starting from the "first well-documented" securities manipulation fraud, known as the "Dutch Tulip Mania" in 1636 and 1637 in the Netherlands, to 'Glaxo China' in 2014, corporate frauds around the world, have rocked the corporate world resulting, either in new or revamping of the older governance structures, codes and guidelines. This paper aims to categorize prominent factors responsible for corporate collapses and that too of reputedly sound corporate giants during the period 1990-2014. Review and analyses of 55 cases from 16 countries identify USA as the country highest in corporate frauds with 53% of the cases going to its credit. In 83% of the corporate collapses, the Chief Executive Officers (CEOs) in collusion with 77% of the Chief Financial Officers (CFOs) have been held responsible. In 72 % of the cases, the main players have faced criminal penalties and were sentenced to jail, whereas 69% received monetary penalties. A number of factors including greed and over ambitiousness of the top executives and poor internal controls have found to be prominent causes of corporate collapses. All the corporations that collapsed, were corporate giants in their own fields, had strong market repute and rich annual reports. But all fell a prey to, either over ambitiousness or to greed of their top notch executives, who indulged in high risk ventures in order to expand. In major corporate scandals, stakeholders apparently were misled by sound annual reports, while the facts later on revealed presence of gross management misconduct, fraudulent financial reporting and auditing issues. The aggressive and speedy growth and expansion of any corporation, has been found to be a common warning sign that should be examined skeptically by any shareholder or investor before investing.
Keywords: 330; corporate governance; governance theories; corporate scams; modi operandi; CG failings